Reading Circle for verbal reasoning and critical thinking at UCLA (Mayéutica Revista Científica de Humanidades y Artes, 2017)
Critical thinking is part of the generic competences that an university student must possess, for their effective inclusion in the professional field; hence, the interest of this research in analyzing the experience of the Reading circle, for the development of critical thinking in university students with the purpose of strengthening academic learning, focusing on the ability of verbal reasoning and arguments analysis. The research is based on a qualitative approach, its methodology is hermeneutics of a literary nature. The participant observation, the semistructured interview and the focal groups were used as collection techniques of data. The actors of the investigation were students from the 1st semester of the Degree in Human Development of the university called: Universidad Centroocidental Lisandro Alvarado during the period (2013- 2) The method applied to the interpretation of the results corresponded to discourse analysis (Casalmilgia and Tuson, 2001). In our research context, the dimensions addressed were verbal ability, handling of arguments and the relevance of the strategy. The dimensions of discourse analysis oral discourse were also taken into account, these are: thematic dimension and enunciative dimension. Among the final considerations, it is emphasized that the "reading circle" is an experience that allows the development of verbal and written reasoning skills as dimensions of students' critical thinking, since the phases of reading and the high degrees of abstraction and reflection that it allows are being taken into account.
Keywords: Reading circle; critical thinking; human development